Solutions of the time fractional reaction-diffusion equations with residual power series method - Tchier, Fairouz; İnç, Mustafa; Korpinar, Zeliha S.; Baleanu, Dumitru (Sage Publications Ltd, 2016)
In this article, the residual power series method for solving nonlinear time fractional reaction-diffusion equations is introduced. Residual power series algorithm gets Maclaurin expansion of the solution. The algorithm is tested on Fitzhugh-Nagumo and generalized Fisher equations with nonlinearity ranging. The solutions of our equation are computed in the form of rapidly convergent series with easily calculable components using Mathematica software package. Reliability of the method is given by graphical consequences, and series solutions are used to illustrate the solution. The found consequences show that the method is a powerful and efficient method in determination of solution of the time fractional reaction-diffusion equations.
Keywords: Residual power series method; time fractional Fitzhugh-Nagumo equation; time fractional non-homogeneous reaction-diffusion equation; two-dimensional time fractional Fisher equation; series solution